2015
DOI: 10.1242/jeb.110809
|View full text |Cite
|
Sign up to set email alerts
|

The expanding epigenetic landscape of non-model organisms

Abstract: Epigenetics studies the emergence of different phenotypes from a single genotype. Although these processes are essential to cellular differentiation and transcriptional memory, they are also widely used in all branches of the tree of life by organisms that require plastic but stable adaptation to their physical and social environment. Because of the inherent flexibility of epigenetic regulation, a variety of biological phenomena can be traced back to evolutionary adaptations of few conserved molecular pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 125 publications
(130 reference statements)
0
36
0
1
Order By: Relevance
“…Epigenetic variations are molecular modifications that alter gene expression, but not the underlying DNA sequence, and occur in the form of histone modifications, non-coding RNAs, and DNA methylations (Bossdorf et al, 2008;Berger et al, 2009). Recent studies in the young research field of Ecological Epigenetics provide increasing evidence for the potential of epigenetic variation to increase plasticity, facilitate speciation and accelerate adaptation to new environments and stressful conditions (Schrey et al, 2013;Bonasio, 2015;Verhoeven et al, 2016;Kilvitis et al, 2017;Richards et al, 2017).…”
Section: A2 Epigenetic Potential To Adapt To Climate Changementioning
confidence: 99%
“…Epigenetic variations are molecular modifications that alter gene expression, but not the underlying DNA sequence, and occur in the form of histone modifications, non-coding RNAs, and DNA methylations (Bossdorf et al, 2008;Berger et al, 2009). Recent studies in the young research field of Ecological Epigenetics provide increasing evidence for the potential of epigenetic variation to increase plasticity, facilitate speciation and accelerate adaptation to new environments and stressful conditions (Schrey et al, 2013;Bonasio, 2015;Verhoeven et al, 2016;Kilvitis et al, 2017;Richards et al, 2017).…”
Section: A2 Epigenetic Potential To Adapt To Climate Changementioning
confidence: 99%
“…Epigenetic studies using non-model animals have increased in the last few years (Perfus-Barbeoch et al, 2014;Bonasio, 2015;Metzger and Schulte, 2016;Verhoeven et al, 2016). This emerging data has allowed investigators to assess the role of epigenetic mechanisms in an environmental and ecological context (Ledón-Rettig, 2013).…”
Section: Epigenetics-a Brief Overviewmentioning
confidence: 99%
“…This epigenetic mark (sensu Feng et al, 2010) has increasingly been the focus of studies in ecological epigenetics in non-model systems and plants (Schrey et al, 2013;Bonasio, 2015;Metzger and Schulte, 2016;Verhoeven et al, 2016) and increasingly in marine metazoans. Biochemically, DNA methylation involves the addition of a methyl group (CH 3 ) to the pyrimidine ring of cytosines within CG dinucleotides (CpGs) resulting in 5-methylcytosine (5mC).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Although at the time of Waddington, the mechanisms of this phenomenon were, of course, unknown, his definition was supplanted over the years. In the last decade, epigenetic mechanisms have been most intensively investigated in areas like cell differentiation of eukaryotes (Bonasio 2015) and development and treatment of cancer and other diseases (Ptak and Petronis 2008). These studies revealed three major levels of epigenetic regulation: (i) DNA methylation, (ii) chromatin remodeling by histone modification, and (iii) RNA interference.…”
Section: Introductionmentioning
confidence: 99%